Asuhan Keperawatan Pada Tn. I Dengan Stroke Di Ruangan Pejuang Rumah Sakit Umum Daerah (RSUD) Bangkinang - Puspita, Dela; Hidayat, Ridha (Jurnal Spektrum Kesehatan Indonesia, 2025)
Stroke  is  a  cerebrovascular  disorder  that results  in  reduced  blood  flow to the brain, potentially causing disability or death. This study aims to describe the implementation of nursing care for a stroke patient based on the nursing process approach, which includes assessment, nursing diagnosis, intervention, implementation, and evaluation. A case study was conducted on Mr. I, a stroke patient treated in the Pejuang Ward of Bangkinang Regional General Hospital (RSUD Bangkinang) over a three-day period, from May 1 to May 3,  2025.The  assessment revealed  symptoms such as  left-sided  limb  weakness, slurred speech, high blood pressure, and intermittent headaches. Nursing diagnoses included risk of ineffective cerebral perfusion, acute pain, nutritional deficit, impaired physical mobility, and anxiety. Interventions were carried out according to the Indonesian Nursing Intervention Standards (SIKI), and evaluations indicated improvements in patient condition, including increased consciousness, reduced pain, and improved mobility.This study highlights the importance of comprehensive and continuous nursing care for stroke patients to enhance quality of life and prevent complications. The findings are expected to serve as a reference for nursing management of stroke patients in hospital settings.